Safety pharmacology assessment of Ethanamizuril, a novel triazines coccidiostat. (October 2020) - Wang, Chunmei; Liu, Yingchun; Zheng, Haihong; Li, Yang; He, Jun; Wang, Xiaoyang; Wang, Mi; Zhang, Lifang; Xue, Feiqun; Zhang, Keyu
Abstract: In the current study, to support the safety pharmacology assessment of Ethanamizuril as a new potent anticoccidial agent of triazine compounds, the effects of Ethanamizuril on the central nervous system, cardiovascular system and respiratory system were investigated. Using locomotor activity test, climbing behavior test and nembutal subthreshold hypnotic test at each time point after oral administration of Ethanamizuril to mice, the effects on the central nervous system were evaluated. An assessment of Ethanamizuril effects on the cardiovascular and respiratory system were performed by the use of a telemetry system in conscious beagle dogs. The results showed that the treatment of Ethanamizuril had no effects on motor activity, behavioral changes, coordination, and sensory/motor reflex responses in mice. There were also no changes in heart rate, blood pressure, and electrocardiogram at all doses and each time points in beagle dogs. Our data suggested that Ethanamizuril showed no adverse effects on the central nervous system, cardiovascular system, and respiratory system. Highlights: A safety pharmacology study of triazines coccidiostats was conducted for the first time. No adverse effects caused by Ethanamizuril in the respiratory, cardiovascular and central nervous systems were found. It provides a reliable basis for the safe use of Ethanamizuril in future.